A New Technique to Supply Fast Varying Reactive Power Using a STATCOM - Tatiana Mariano Lessa de Assis; Edson Hirokazu Watanabe; Luiz Alberto da Silva Pilotto; Raul Balbi Sollero (Eletrônica de Potência)
This paper proposes a new technique to compensate fast oscillating reactive power using a multipulse STATCOM. It is shown that the oscillating reactive power can be controlled in a simple way by maintaining the STATCOM dc voltage constant. A simplified analytical analysis was performed in a power system with an arc furnace and a 12-pulse STATCOM. The study has shown that the STATCOM can compensate the furnace reactive current, even when fast oscillations occur. The system studied was implemented in a detailed EMTP/ATP simulation program. The results show that the reactive power oscillations produced by the furnace can be strongly reduced. However, due to the fact that arc furnace is an unbalanced load, STATCOM dc side capacitor has to be designed to supply the corresponding oscillating energy.